Evaluating the Impact of Plant Growth Hormones on Growth and Yield of Summer Squash - Gelal, Riya; Bhattarai, Supekshya; Thakur , Manish Kumar (Nepalese Journal of Agricultural Sciences, 2025)
The field experiment was conducted at the Directorate of Agricultural Research, Tarahara, Sunsari, during the summer months of March to May 2023 to study the effect of plant growth hormone on the growth and yield of squash (Cucurbita pepo L.). It was a randomized complete block design (RCBD) experiment with six treatments and four replications. The treatments included T1 (NAA - 50 PPM), T2 (NAA - 100PPM), T3 (NAA - 150PPM), T4 (control), T5 (GA3 - 100PPM), and T6 (GA3 - 150PPM) Observations showed that plants treated with GA3 at 150 PPM (T6) exhibited maximum height and an increased number of branches at 45 DAS. Additionally, the highest fruit yield per plant (884.95 g) was obtained from plants receiving the recommended NPK concentration (200:180:80 kg/ha) (T6). The greatest fruit length and diameter were recorded in T1 and T6, measuring 22 cm and 77.4 mm, respectively. Growth and yield parameters were considerably lower in the control plot. Therefore, it can be concluded that treatment T6 (GA3 at GA3-150 ppm) showed a superior effect on the growth and yield of summer squash compared to other treatments, and its application in the field could help increase production and productivity.